Comparative Study of Surgical Site Infections and Antimicrobial Resistance with Focus on Carbapenem Resistant Klebsiella pneumoniae - Maharjan, Renuka; Dewasy, Bijoy Lakshmi; Singh, Randhir Kumar; Tuladhar, Reshma; Singh, Praveer Raj; Pokharel, Hanoon P; Singh, Anjana (Tribhuvan University Journal of Microbiology, 2025)
Objectives: The aim of this study evaluates the trends in surgical site infections (SSIs), bacterial distribution, antimicrobial resistance, and molecular detection of resistance genes in two different phases. Methods: The clinical specimens were collected from SSIs patients in both phases. The bacteria was isolated using standard microbiological techniques and further identified by the VITEK 2 system. Phenotypic screening for carbapenemase was conducted through Modified carbapenem inactivation method (mCIM) while presence of blaKPC, acrA, and acrB genes were detected by PCR. Results: In phase two, the SSIs rate reduced by 33% particularly due to improvement in prophylactic practices. The number of isolated bacteria decreased by 73.13%, with Gram-negative bacteria remaining predominant. The study reported significant increase in resistance in Klebsiella pneumoniae particularly to amikacin (100%), colistin (80%), and tigecycline (20%) whereas found 100% susceptible to doripenem. All carbapenem resistant K. pneumoniae were found mCIM positive but blaKPC negative, while acrA and acrB genes were detected in all the isolates. Conclusion: Implementation of improved antimicrobial prophylaxis guidelines resulted in a significant reduction in infection rates. However, an increase in antimicrobial resistance among K. pneumoniae was observed. Although the blaKPC gene was not detected in carbapenem-resistant isolates, the presence of efflux pump genes in all resistant strains suggests their contributory role in resistance. These findings underscore the urgent need for strengthened antibiotic stewardship and continuous surveillance of resistance mechanisms to curb antimicrobial resistance in surgical settings.